Earliest Cretaceous cocoons or plant seed structures from the Wealden Group, Hastings, UK - Brasier, AT; Cotton, LJ; Garwood, RJ; Baker-Brian, J; Howlett, E; Brasier, M (Geological Society of London, 2017)
Complete metamorphosis evolved in insects towards the end of the Palaeozoic Era. A wide range of pupation strategies existed and numerous biosedimentary structures associated with these have been described. The fossil record of endogenous materials associated with pupation, e.g. cocoons, is more limited. Here we report six amber-coloured specimens from the earliest Cretaceous of southern England that were tentatively identified on collection as insect cocoons. These were analysed by Fourier transform infrared spectrometry, stereomicroscopy and X-ray microtomography to elucidate their origin. The interpretation of the Fourier transform infrared spectrometry data was inconclusive because the spectra showed some differences from those of amber. A seed pod origin seems likely for at least two of the objects based on their size, shape and the lineations on their surfaces. Three specimens are more cocoon-like based on their overall morphology and a fibrous surface texture. Although plant megaspore membranes have features analogous with these specimens and cannot be ruled out, the similarity to and variability found within insect cocoons, coupled with the range of potential insect architects present at the time of origin, make an insect origin more likely. We review a number of hymenopteran clades whose extant members construct comparable cocoons. The possible cocoons may have been resin-coated to protect the larva inside from predation, or they may have passively come into contact with resin prior to burial. Supplementary material: All TIFF computed tomography slices from the scan, the computed tomography log file, a surface model of the specimen and digital visualizations of both the whole specimen and the perforations are available at https://doi.org/10.6084/m9.figshare.c.3704794